Gene expression profiling in hearts of diabetic mice uncovers a potential role of estrogen-related receptor γ in diabetic cardiomyopathy. (15th July 2016) - Lasheras, Jaime; Vilà, Maria; Zamora, Mònica; Riu, Efrén; Pardo, Rosario; Poncelas, Marcos; Cases, Ildefonso; Ruiz-Meana, Marisol; Hernández, Cristina; Feliu, Juan E.; Simó, Rafael; García-Dorado, David; et al.
Abstract: Diabetic cardiomyopathy is characterized by an abnormal oxidative metabolism, but the underlying mechanisms remain to be defined. To uncover potential mechanisms involved in the pathophysiology of diabetic cardiomyopathy, we performed a gene expression profiling study in hearts of diabetic db/db mice. Diabetic hearts showed a gene expression pattern characterized by the up-regulation of genes involved in lipid oxidation, together with an abnormal expression of genes related to the cardiac contractile function. A screening for potential regulators of the genes differentially expressed in diabetic mice found that estrogen-related receptor γ (ERRγ) was increased in heart of db/db mice. Overexpression of ERRγ in cultured cardiomyocytes was sufficient to promote the expression of genes involved in lipid oxidation, increase palmitate oxidation and induce cardiomyocyte hypertrophy. Our findings strongly support a role for ERRγ in the metabolic alterations that underlie the development of diabetic cardiomyopathy. Highlights: db/db mice are a good model for the study of early diabetic cardiomyopathy. Diabetic heart is characterized by an exacerbated expression of genes related to lipid metabolism. ERRγ is a major regulatory node of the gene network related to lipid metabolism in diabetic heart. ERRγ overexpression in cardiomyocytes increases lipid oxidation and induces cell hypertrophy.